In situ strain and temperature measurement and modelling during arc welding. (18th March 2015) - Chen, J.; Yu, X.; Miller, R. G.; Feng, Z.
Abstract : Experiments and numerical models were applied to investigate the thermal and mechanical behaviours of materials adjacent to the weld pool during arc welding. In the experiment, a new high temperature strain measurement technique based on digital image correlation (DIC) was developed and applied to measure the in situ strain evolution. In contrast to the conventional DIC method that is vulnerable to the high temperature and intense arc light involved in fusion welding processes, the new technique utilised a special surface preparation method to produce high temperature sustaining speckle patterns required by the DIC algorithm as well as a unique optical illumination and filtering system to suppress the influence of the intense arc light. These efforts made it possible for the first time to measure in situ the strain field 1 mm away from the fusion line. The temperature evolution in the weld and the adjacent regions was simultaneously monitored by an infrared camera. Additionally, a thermal–mechanical finite element model was applied to substantiate the experimental measurement.